Equipping Youth: Membangun Kesuksesan Remaja JKI Keluarga Kerajaan Salatiga melalui Manajemen Diri dan Peningkatan Kepercayaan Diri - Hizkia Bryan Hulu; Clarischa Geovani Raharja; Sabrina Dwi Cahya; Aloysius G. Tamaka; Rizki Amalia Yanuartha Yanuartha (Universitas Kristen Satya Wacana Salatiga, 2025)
Self-management and increasing self-confidence are crucial elements in shaping teenagers' success, enabling them to manage stress, develop leadership skills, and build a solid foundation for achieving life goals. Increasing self-confidence is the main key to achieving goals, increasing intrinsic motivation, and overcoming obstacles with belief in one's potential. This research explores the central role of self-management and increasing self-confidence in shaping adolescent success, especially in the JKI Keluarga Kerajaan. In addressing the unique challenges of adolescents in this environment, researchers implemented a specially designed Equipping program. The impact of equipping is reflected in the youth's ability to appear in the 7-minute sermon at every Kingdom Generation service on Sunday. This research is expected to provide in-depth insight into the important role of self-management and self-confidence in shaping adolescent success, especially in the context of spiritual life and ecclesial service.